2017
DOI: 10.1136/rmdopen-2017-000438
|View full text |Cite
|
Sign up to set email alerts
|

Effect of celastrol on bone structure and mechanics in arthritic rats

Abstract: ObjectiveRheumatoid arthritis (RA) is characterised by chronic inflammation leading to articular bone and cartilage damage. Despite recent progress in RA management, adverse effects, lack of efficacy and economic barriers to treatment access still limit therapeutic success. Therefore, safer and less expensive treatments that control inflammation and bone resorption are needed. We have previously shown that celastrol is a candidate for RA treatment. We have observed that it inhibits both interleukin (IL)-1β and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 53 publications
(50 reference statements)
2
12
0
Order By: Relevance
“…In contrast, the addition of Cel had not contributed any significant changes in HPLF proliferation. Previously, Cascão et al . reported that intraperitoneal administration of Cel to female Wistar adjuvant‐induced arthritic rats decreased the osteoblasts number in arthritic joints.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the addition of Cel had not contributed any significant changes in HPLF proliferation. Previously, Cascão et al . reported that intraperitoneal administration of Cel to female Wistar adjuvant‐induced arthritic rats decreased the osteoblasts number in arthritic joints.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier in vitro and in vivo studies revealed that Res treatment significantly reduced bone loss due to trauma by reducing osteoclastogenic regulatory genes in periodontal ligament tissue and the differentiation of osteoclastogenic precursors (BMM and RAW 264.7 cells) . Intraperitoneal administration of Cel reduced both bone resorption and cartilage degradation in female Wistar adjuvant‐induced arthritic rats …”
Section: Resultsmentioning
confidence: 99%
“…Normality distribution was assessed by D'Agostino and Pearson test. The treated groups (celastrol 1, 2.5, 5, and 7.5 ug/g) were compared against the untreated arthritic group with the Mann-Whitney test with Bonferroni correction to account for multiple comparisons, as previously reported (17). Thus, applying the Bonferroni correction, we divided the global significance level at 0.05 by the number of independent tests (n = 4) to get the Bonferroni critical value of p < 0.0125, below which a test would be significant.…”
Section: Discussionmentioning
confidence: 99%
“…Celastrol was also reported to attenuate bone erosion in collagen-induced arthritis mice and inhibits osteoclast differentiation and function in RANKL-induced RAW264.7 [ 39 ]. In the microfluidic device, celastrol inhibited SW982 migration and simultaneously suppressed TRAP activity in RAW264.7 cells, suggesting a cellular mechanism of celastrol by which celastrol exerted an effective treatment in RA rats through preventing bone loss and bone microarchitecture degradation [ 40 ]. We also found that celastrol did not enhance ALP activity of BMSC.…”
Section: Discussionmentioning
confidence: 99%